Dissociative identity disorder in the characters Mima and Rumi from Satoshi Kon's Perfect Blue - Villeneuve, Bianca Cynara; Puspitasari, Diana; Kadafi, Muammar (Universitas Dian Nuswantoro, 2023)
The purpose of this study is to describe the Dissociative Identity Disorder (DID) of the character Mima and Rumi, from “Perfect Blue” created by Satoshi Kon. The research approach is descriptive and qualitative. The data collection method involves observation and note-taking. The data analysis technique used is content analysis, where acquired data is analyzed to draw conclusions. Based on the research findings, 37 instances of DID data were identified, consisting of 3 instances of amnesia, 9 instances of depersonalization, 13 instances of derealization, 3 instances of identity crisis data, and 9 instances of identity change data. The conclusion emphasizes the fact that both Mima and Rumi experience symptoms of Dissociative Identity Disorder, such as amnesia, depersonalization, derealization, identity crisis, and changes in identity. This study contributes to a deeper understanding of the complexity of the characters, offering insights into the portrayal of DID in fiction.